Crystal Structure of an Unexpected Oxime-Type Polymer (C10H11BrNO)n - Li, Xiao-Bing; Li, Gang; Zhang, Yu-Jie; Dong, Xiu-Yan (Asian Journal of Chemistry, 2013)
An oxime-type polymer, (C10H11BrNO)n, has been unexpectedly obtained in the process of synthesis of bis(3-bromobenzaldehyde)O,O'-(hexane-1,6-diyl)dioxime. The crystal structure of the title compound has been determined by single-crystal X-ray diffraction method. The title compound crystallizes in a monoclinic crystal system, space group P2(1), with a = 4.1460(5), b = 5.4641(7), c = 22.030(2) Å, b = 91.230(1)º and Z = 2. And the polymer chains take a herringbone fashion.